2022
DOI: 10.1177/21677026211071091
|View full text |Cite
|
Sign up to set email alerts
|

Gray-Matter Morphometry of Internalizing-Symptom Dimensions During Adolescence

Abstract: Understanding the neuroanatomical correlates of internalizing psychopathology during adolescence may shed light on neurodevelopmental processes that make this a critical period for the trajectory of mental illness. However, few studies have simultaneously examined co-occurring and dissociable features of internalizing psychopathology during this formative developmental stage. In the current study, we identify the neuroanatomical correlates of four dimensions of internalizing psychopathology symptoms in adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…These null findings may be a function of our sample, who have not yet reached the age for the typical onset of mood disorders and suicidality. Nevertheless, the preliminary signals we were able to identify may be important threads to follow up on in future research in this sample as they progress through adolescence, as many of the ROIs highlighted (e.g., lingual gyrus, isthmus cingulate, precuneus, fusiform gyrus) have been implicated in research on internalizing symptoms, depression, and suicidality in adolescence and adulthood ( Cheng et al, 2018 , Jung et al, 2014 , Ries et al, 2009 , Smolker et al, 2022 , Westlund Schreiner et al, 2019 , Wiglesworth et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These null findings may be a function of our sample, who have not yet reached the age for the typical onset of mood disorders and suicidality. Nevertheless, the preliminary signals we were able to identify may be important threads to follow up on in future research in this sample as they progress through adolescence, as many of the ROIs highlighted (e.g., lingual gyrus, isthmus cingulate, precuneus, fusiform gyrus) have been implicated in research on internalizing symptoms, depression, and suicidality in adolescence and adulthood ( Cheng et al, 2018 , Jung et al, 2014 , Ries et al, 2009 , Smolker et al, 2022 , Westlund Schreiner et al, 2019 , Wiglesworth et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Internalizing symptoms have been linked to reduced gray matter volumes in the insula in middle childhood ( Snyder et al, 2017 ) but decreased thinning in the orbital frontal cortex in late childhood ( Pfeifer and Allen, 2021 , Whittle et al, 2020 ). In adolescence, internalizing symptoms are associated with greater fusiform gyrus CT for male and female youth and superior frontal gyrus volumes for male, but not female, youth ( Smolker et al, 2022 ). Further, less surface area of frontal, temporal, and parietal regions ( Gifuni et al, 2021 ), as well as smaller volumes in the right superior temporal gyrus ( Pan et al, 2015 ), are cross-sectionally associated with histories of suicidal behavior in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Both models fit the data well and each factor was associated with diagnostic status for a range of internalizing disorders, including major depressive disorder (MDD) and generalized anxiety disorder (GAD). Follow-up work demonstrated that this factor structure replicates across samples and that the dimensions have distinct neural correlates, providing external validity to each dimension (Banich et al, 2020; Smolker et al, 2022).…”
Section: Dimensional Models Of Internalizing Symptoms and Repetitive ...mentioning
confidence: 83%
“…Through confirmatory factor analyses of correlated factors models, Nitschke et al (2001) demonstrated that this expanded model better accounted for variability in symptoms of anxiety than the original model (see first diagram in panel A of Figure 1 for expanded model). Recent research on this model has shifted away from correlated factors models to instead quantify the internalizing symptom dimensions through bifactor and hierarchical parameterizations (e.g., Banich et al, 2020;Smolker et al, 2022;Snyder et al, 2022). These parameterizations are advantageous over correlated factors in their ability to quantify general factors that affect multiple aspects of psychopathology, and, in the case of the bifactor model, also capture dimension-specific factors.…”
Section: Four-factor Model Of Internalizing Symptommentioning
confidence: 99%
See 1 more Smart Citation